Knowledge, Awareness, and Perception of Dentists towards implant preference - Mariam, Sarah; Halli , Raj Shekhar; Khalique, Najam (Indian Journal of Community Health, 2025)
Background: There is a dearth of evidence from the providers (dentists’) perspective, their attitudes, cognitive knowledge toward implant treatment and maintenance. This can impact the treatment objectives. Miniscule studies have investigated the qualitative and quantitative analysis of population of dentists’ in shifting from crown and bridge practice to dental implant therapy and oral hygiene related to dental implants. Aims & objectives: To evaluate knowledge, perception and awareness of dentists’ in shifting from crown and bridge practice to dental implant therapy in Pune city. Methodology: A self-administered validated 24- item questionnaire, was administered among general, academic and non-academic practitioners. Descriptive analysis was done. Results: Dental implants are the treatment of choice (55.6%) over crown and bridge. Majority of participants had an overall better knowledge regarding practice of implant-based dentistry over crown and bridge but not regarding periimplantitis. Conclusion: Our study showed that dental practitioners in Pune possess good knowledge of dental implant as a therapeutic option. However knowledge about parameters for assessing oral hygiene around implants was inadequate.